AB0214 Methotrexate in early rheumatoid arthritis: a single-center evaluation of clinical outcome comparing two starting treatment strategies. (15th June 2017) - Benaglio, F; Bugatti, S; Sakellariou, G; Crepaldi, G; Zanframundo, G; Montecucco, C; Caporali, R
Abstract : Background: methotrexate (MTX) is considered the 'anchor drug' in the treatment of rheumatoid arthritis (RA) and it should be part of the first treatment strategy: there are many indications about the correct way to optimize the dosage, depending on clinical response and tolerability, but currently there is no shared evidence about the optimal starting dosage. Objectives: to compare two different starting treatment strategies with MTX in patients with early RA evaluated at our Early Arthritis Clinic (EAC) in order to assess the rate of patients who reaches the target (remission/low disease activity) at 6 months, according with EULAR guidelines. Methods: patients with RA (disease duration <12 months) evaluated at our EAC between 2005 and 2016 and treated with MTX parenterally and glucocorticoids (GC) were included. Patients followed a treat-to-target strategy to reach low disease activity with bimonthly tight control. Patients evaluated between 2005 and 2009 were initially treated with MTX 10 mg/week + GC (group A) with increase of MTX to 15 and then 20 mg/week in case of failure to reach the target; patients evaluated between 2010 and 2016 were initially treated with MTX 15 mg/week + GC (group B) with possible increase to 20 and 25 mg/week. The DAS28 response was assessed after 6 months. Results: 260 patients were analyzed: 123 in group A vs 137 in group B. At baseline patients showed differences in DAS28 (5.2±1.15 vs 4.6±1.16, p<0.0001) and HAQ (1, 125 vs 1 IQR IQR 0.75–1.875 0.375–1.5, p=0.006); there were no differences in terms of autoimmunity. After 6 months of therapy there were no differences in clinical response: 32% of patients in the group A reached the DAS28 remission vs 40% of the group B (p= ns), 27% in the group A reached the DAS28 low disease activity vs 24% of the group B (p= ns), 41% of the group A was in moderate disease activity vs 36% in the group B (p= ns). The need to increase the dosage of MTX during the first 6 months was similar: 27.6% of the group A vs 29.9% of the group B (p= ns), conversely, the need to reduce the dosage of MTX due to intolerance and/or adverse event was significantly higher in the group B (group A: 1.6% vs group B: 9.5%, p=0.014). Conclusions: the use of higher dose of MTX is associated with a higher rate of side effects but does not provide, at short term, a significant improvement in term of clinical outcome. Conversely, the initial use of MTX 10 mg/week, with a quick dose titration in case of persistent disease activity, seems to be an appropriate option for many patients with early RA, as also recently suggested by the Utrecht Arthritis Cohort Study Group; in spite of this, there is an amount of patients who do not achieve the clinical target at short term regardless of the initial dose of MTX. Our experience suggests that in the early phase of RA treatment, in a context based on early diagnosis, tight control and treat to target, the clinical outcome seems to be linked more to the treatment strategy than to the drug dosage used. References: Combe B, et al. 2016 update of the EULAR recommendations for the management of early arthritis. Ann Rheum Dis-2016–210602. Nair SC, et al. Determining the lowest optimally effective methotrexate dose for Individual RA patients using their dose response relation in a tight control treatment approach. PLoS ONE 11:e0148791. Disclosure of Interest: None declared